2021
DOI: 10.1186/s12866-021-02143-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clostridium butyricum on growth performance, metabonomics and intestinal microbial differences of weaned piglets

Abstract: Background Weaning stress of piglets causes a huge economic loss to the pig industry. Balance and stability of the intestinal microenvironment is an effective way to reduce the occurance of stress during the weaning process. Clostridium butyricum, as a new microecological preparation, is resistant to high temperature, acid, bile salts and some antibiotics. The aim of present study is to investigate the effects of C. butyricum on the intestinal microbiota and their metabolites in weaned piglets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 99 publications
4
25
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to examine the effects of dietary C. butyricum supplementation in a high-concentrate diet on growth performance in fattening goats. The results showed no significant improvement in daily gain, which is consistent with the results for weaned piglets, in which no significant improvement in growth performance was found during the 21-day observation period ( 27 , 28 ). However, we found that most of the studies on the growth performance of C. butyricum in monogastric animals reported beneficial results ( 29 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to examine the effects of dietary C. butyricum supplementation in a high-concentrate diet on growth performance in fattening goats. The results showed no significant improvement in daily gain, which is consistent with the results for weaned piglets, in which no significant improvement in growth performance was found during the 21-day observation period ( 27 , 28 ). However, we found that most of the studies on the growth performance of C. butyricum in monogastric animals reported beneficial results ( 29 ).…”
Section: Discussionsupporting
confidence: 89%
“…The rumen pH was significantly increased with the increase in C. butyricum dose in the HCB group compared with the LCB group. Recent studies have shown that C. butyricum protects intestinal barrier function and the immune response by regulating the microbiome ( 12 , 27 , 36 , 37 ). To our knowledge, this is the first study to investigate the microbiota of goats fed C. butyricum .…”
Section: Discussionmentioning
confidence: 99%
“…Results also revealed that the ADG of group CB400 increased significantly (p < 0.05) in comparison with group Con; and the FCR of group CB200 and group CB400 reduced significantly (p < 0.05) in comparison with results for group Con (Table 2). 1 Means with different superscript letters indicate that there are significant differences (p < 0.05) between any two groups in the same row. 2 ABW: average body weight, ADG: average daily gain, ADFI: average daily feed intake, FCR: feed conversion ratio, Group Con: the control group, Group A150: the aureomycin group.…”
Section: Effect Of C Butyricum and Aureomycin On Growth Performance Of Pekin Duckmentioning
confidence: 99%
“…On day 42, the concentrations of acetate in group CB400 and CB600, propionate in group CB400, butyrate in group CB400 and A150, iso-butyrate and iso-valerate in all groups increased (p <0.05) significantly in comparison with group Con (Table 3). 1 Means with different superscript letters indicate that there are significant differences (p < 0.05) between any two groups in the same row, Group Con: the control group, Group A150: the aureomycin group. 2 Total SEM (N = 10).…”
Section: Effect Of C Butyricum and Aureomycin On Fecal Scfasmentioning
confidence: 99%
See 1 more Smart Citation